The resource-based view of the firm: Ten years after 1991 - Barney, Jay; Wright, Mike; Ketchen, David J. (Journal of Management, 2001)
At present, the resource-based view of the firm is perhaps the most influential framework for understanding strategic management. In this editor’s introduction, we briefly describe the contributions to knowledge provided by the commentaries and articles contained in this issue. In addition, we outline some additional areas of research wherein the resource-based view can be gainfully deployed.